The cross-cultural validation of the Beach Center Family Quality of Life Scale among persons affected by leprosy or podoconiosis in Northwest Ethiopia. - Moges Wubie Aycheh; Anna T Van't Noordende; Nurilign Abebe Moges; Alice P Schippers (Public Library of Science (PLoS), 2023)
Background The Beach Center Family Quality of Life Scale has been developed and validated in different languages in different countries. However, this scale has not been validated in the Ethiopian Amharic language context. Therefore, this study aimed to investigate the cross-cultural validity of the Beach Center Family Quality of Life Scale, among Ethiopian families of persons affected by leprosy and podoconiosis. Methodology We explored the semantic equivalence, internal consistency, reproducibility, floor and ceiling effects, and interpretability of the Beach Center Family Quality of Life Scale in Amharic. A cross-sectional study was conducted after the translation and back-translation of the instrument. A total of 302 adult persons affected by leprosy or podoconiosis was asked about their level of satisfaction with their family life, using the Beach Center Family Quality of Life Scale. In addition, 50 participants were re-interviewed two weeks after the initial assessment to test the reproducibility of the scale. Participants were recruited in the East Gojjam zone of Northwest Ethiopia. Results The findings of this study showed that the Beach Center Family Quality of Life Scale had high internal consistency (Cronbach's alpha of 0.913) and reproducibility (intra-class correlation coefficient of 0.857). The standard error of measurement was 3.01, which is 2.4% of the total score range. The smallest detectable change was 8.34. Confirmatory factor analysis showed adequate factor loadings and model fit indices like the original scale. The composite reliability and average variance extracted from the scale were acceptable. No floor and ceiling effects were found. Conclusions Our findings indicate that the Amharic version of the Beach Center Family Quality of Life Scale has adequate cultural validity to assess the family quality of life in Ethiopian families of persons affected by leprosy and podoconiosis.